The Sun Today - Vita-Finzi, Claudio (Springer International Publishing, 2018)
From the reviews of other books by Claudio Vita-Finzi: The Sun - A User's Manual (2008) ....this, jargon-free, concise, beautifully illustrated and eminently readable book... D.W. Hughes, Times Literary Supplement Solar History (2013) ....a book that is supremely informative, intensely stimulating and enjoyable to read... Ian Seymour, Astronomy Now A History of the Solar System (2016) ...there is a huge amount of useful information in this book that would benefit anyone who needed more detail than is available in a typical popular science title. Brian Clegg, Popular Science.